2022
DOI: 10.1186/s13054-022-04090-1
|View full text |Cite
|
Sign up to set email alerts
|

The gut–liver axis in sepsis: interaction mechanisms and therapeutic potential

Abstract: Sepsis is a potentially fatal condition caused by dysregulation of the body's immune response to an infection. Sepsis-induced liver injury is considered a strong independent prognosticator of death in the critical care unit, and there is anatomic and accumulating epidemiologic evidence that demonstrates intimate cross talk between the gut and the liver. Intestinal barrier disruption and gut microbiota dysbiosis during sepsis result in translocation of intestinal pathogen-associated molecular patterns and damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 171 publications
0
27
0
1
Order By: Relevance
“…The levels of butyric acid were decreased in critical patients, which was closely related to the reduction in butyrate-producing bacteria in septic patients (10). Because of the protective role of butyric acid in intestinal integrity, immune responses, liver injury, and brain injury (28–30), the lower abundance of butyrate-producing bacteria might be a risk factor for sepsis onset (10). In the current study, we observed decreasing trends in fecal SCFAs from septic patients over 3 weeks upon ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of butyric acid were decreased in critical patients, which was closely related to the reduction in butyrate-producing bacteria in septic patients (10). Because of the protective role of butyric acid in intestinal integrity, immune responses, liver injury, and brain injury (28–30), the lower abundance of butyrate-producing bacteria might be a risk factor for sepsis onset (10). In the current study, we observed decreasing trends in fecal SCFAs from septic patients over 3 weeks upon ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical study has found that gut microbiota is associated with 28-day mortality among critically ill patients [22]. Given the interactions with various organs, the gut dysbiosis and compromised intestinal barrier integrity deeply participate in the development and exacerbation of critical illness [23][24][25]. Since the gut dysbiosis has profound effects on the development, maintenance, and outcomes of sepsis [26], the different performances of D-lactate, LPS and DAO in our study can be explained that even under similar challenges from IECs damage, patients with gut dysbiosis are more susceptible to compromised intestinal barrier integrity, bacterial translocation and sepsis, and subsequent worse outcome.…”
Section: The Effect Of Compromised Intestinal Barrier Integrity On Di...mentioning
confidence: 99%
“…During critical illness, gastrointestinal transit changes, as well as unique medication and nutrition patterns, can drive dramatic changes in the gut microbiota [ 1 ]. Conversely, a disturbed microbiome provides a niche for the growth of pathogenic microbes, whose components can translocate across an impaired gut barrier and worsen the condition [ 4 ]. Although previous studies have focused on the microbial features of patients with sepsis, the role of bacteria found to be altered in sepsis remains unclear.…”
Section: Introductionmentioning
confidence: 99%